Emerging Cationic Nanovaccines - Ana Maria Carmona-Ribeiro; Yunys Pérez-Betancourt (Pharmaceutics)
Cationic vaccines of nanometric sizes can directly perform the delivery of antigen(s) and immunomodulator(s) to dendritic cells in the lymph nodes. The positively charged nanovaccines are taken up by antigen-presenting cells (APCs) of the lymphatic system often originating the cellular immunological defense required to fight intracellular microbial infections and the proliferation of cancers. Cationic molecules imparting the positive charges to nanovaccines exhibit a dose-dependent toxicity which needs to be systematically addressed. Against the coronavirus, mRNA cationic nanovaccines evolved rapidly. Nowadays cationic nanovaccines have been formulated against several infections with the advantage of cationic compounds granting protection of nucleic acids in vivo against biodegradation by nucleases. Up to the threshold concentration of cationic molecules for nanovaccine delivery, cationic nanovaccines perform well eliciting the desired Th 1 improved immune response in the absence of cytotoxicity. A second strategy in the literature involves dilution of cationic components in biocompatible polymeric matrixes. Polymeric nanoparticles incorporating cationic molecules at reduced concentrations for the cationic component often result in an absence of toxic effects. The progress in vaccinology against cancer involves in situ designs for cationic nanovaccines. The lysis of transformed cancer cells releases several tumoral antigens, which in the presence of cationic nanoadjuvants can be systemically presented for the prevention of metastatic cancer. In addition, these local cationic nanovaccines allow immunotherapeutic tumor treatment.